Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1523/jneurosci.1686-17.2018
|View full text |Cite|
|
Sign up to set email alerts
|

Swedish Nerve Growth Factor Mutation (NGFR100W) Defines a Role for TrkA and p75NTRin Nociception

Abstract: Nerve growth factor (NGF) exerts multiple functions on target neurons throughout development. The recent discovery of a point mutation leading to a change from arginine to tryptophan at residue 100 in the mature NGFβ sequence (NGF) in patients with hereditary sensory and autonomic neuropathy type V (HSAN V) made it possible to distinguish the signaling mechanisms that lead to two functionally different outcomes of NGF: trophic versus nociceptive. We performed extensive biochemical, cellular, and live-imaging e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 163 publications
1
20
0
Order By: Relevance
“…Thus, hNGF R100W protein displays an indistinguishable neurotrophic potency from wild type hNGF, while showing a reduced ability to sensitize sensory neurons. This extends data showing that hNGF R100W uncouples trophic effects from nociceptive functions of NGF [10][11][12] .…”
supporting
confidence: 87%
“…Thus, hNGF R100W protein displays an indistinguishable neurotrophic potency from wild type hNGF, while showing a reduced ability to sensitize sensory neurons. This extends data showing that hNGF R100W uncouples trophic effects from nociceptive functions of NGF [10][11][12] .…”
supporting
confidence: 87%
“…Further studies demonstrated that R100W mutation did not affect NGF binding to TrkA, while it abolished NGF binding to p75 NTR ( Capsoni et al, 2011 ). Our previous study also demonstrated that NGF R100W maintained the ability of binding to and activating the TrkA to support neuronal survival and differentiation ( Sung et al, 2018 ), which could explain why the cognitive impairment of HSAN V patients appeared very limited or absent.…”
Section: Discussionmentioning
confidence: 89%
“…Previous research on NGF R100W revealed that R100W mutation selectively disrupted binding of NGF to p75 NTR , while it retained the ability of binding to TrkA ( Covaceuszach et al, 2010 ; Sung et al, 2018 ). The p75 NTR is transiently synthesized in embryonic kidney ( Sariola et al, 1991 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these motions are not capable of fully activating the biased TrkA signaling, since the R221W mutation inhibits the PLC-γ1 pathway [34], permanently impairing the nociceptive response [33,34,36,37]. Therefore, WT NGF presents a second mechanism to activate the nociception downstream promoted by TrkA, while R221W structures has this mechanism knocked-down as recently raised [57]. Here, we describe the collective motions putatively linked to nociceptive response of TrkA receptors and showed that R221W complex is not capable to reproduce these motions even when the WT motions were forced to the mutant structures.…”
Section: Discussionmentioning
confidence: 99%